2021
DOI: 10.1155/2021/2657689
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Dynamic Deformation of Building Using Unmanned Aerial Vehicle

Abstract: The height irregularity and complexity of steel structures bring difficulties to dynamic deformation monitoring. PDMS (photogrammetric dynamic monitoring system) can obtain the dynamic deformation of the steel structure, but the flexibility of monitoring is limited because the camera station can only be placed on the ground. In this study, UAV (unmanned aerial vehicle) -PDMS is innovatively proposed to be used in monitoring dynamic deformation of steel structures, and it is verified in the steel frame test and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…rough the above experiments and data analysis, it can be found that the problems to be improved in the badminton court in the gymnasium of the school mainly include insu cient lighting and glare [23][24][25]. Regarding the problem, we will improve the badminton court in the school's gymnasium.…”
Section: Improvement Measures For Badminton Courtmentioning
confidence: 94%
“…rough the above experiments and data analysis, it can be found that the problems to be improved in the badminton court in the gymnasium of the school mainly include insu cient lighting and glare [23][24][25]. Regarding the problem, we will improve the badminton court in the school's gymnasium.…”
Section: Improvement Measures For Badminton Courtmentioning
confidence: 94%
“…All the reference points are located on the reference plane. e function of the reference plane is to eliminate systematic errors [10].…”
Section: E Zero-centered Motion Parallax Methodmentioning
confidence: 99%
“…With the development of UAV technology, it is possible to use UAVs to monitor the deformation of buildings [10]. At present, there are abundant research studies on UAV Assisted Structural Health Monitoring (UASHM) [11].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Total station as the representative of the conventional measuring instruments in the building level, vertical, sectional mapping has the advantages of high accuracy and technical maturity [1], but there are high labor costs, inflexible mode of operation, external workload, low efficiency and other deficiencies, and three-dimensional laser scanning technology as a non-contact, active, rapid access to the target object three-dimensional point cloud technology, can directly access a variety of complex, irregular As a non-contact, active and rapid acquisition of 3D point cloud of target objects, 3D laser scanning technology can directly acquire 3D spatial data of various complex and irregular objects or environments, which is expected to improve the efficiency. At present, 3D laser scanning technology has been applied in the fields of section measurement [2], deformation monitoring [3,4] and 3D modeling of buildings [5,6], among which 3D laser scanning technology in longitudinal and transverse section measurement is mainly applied to the section measurement of various tunnels, and few studies have been conducted on the measurement of building sections.…”
Section: Introductionmentioning
confidence: 99%